Characteristics of Inertial Range Turbulent Cascade Rates in the Interplanetary Coronal Mass Ejection - H. Bai; S. Y. Huang; J. Zhang; Z. G. Yuan; H. H. Wu; K. Jiang; Z. Wang; Q. Y. Xiong; R. T. Lin; Y. T. Tang (The Astrophysical Journal)
Interplanetary coronal mass ejections (ICMEs) are different from the typical solar wind in their compressibility and levels of fluctuations in magnetic field, proton velocity, density, and temperature, making them a unique environment for studying turbulence properties. However, the difference between cascade rates in the ICMEs and typical solar wind, the comparison between cascade rates estimated by compressible and incompressible models, and how cascade rates in the ICMEs evolve with the radial distance from the Sun are still unclear. Using the data of 33 ICMEs observed between 0.305 au and 1.015 au by Parker Solar Probe and Solar Orbiter, we statistically investigated the incompressible and compressible inertial range turbulent cascade rates (ϵ _i and ϵ _c ) in and around ICMEs. ϵ _i and ϵ _c in the sheaths and ejecta of ICMEs are always larger than in the upstream solar wind before them. ϵ _i and ϵ _c in the downstream solar wind behind ICMEs can be amplified after the ICMEs pass. ϵ _c is always larger than ϵ _i in all ICME subregions, indicating the amplifying effects of compressibility and levels of fluctuations in proton density, velocity, and temperature on the cascade rates of ICMEs. ϵ _i and ϵ _c in all ICME subregions decrease with the increase of the radial distance. These results shed light on our understanding of turbulent cascade rates and their radial evolution in ICMEs.